Comparison of once a day and three times a day iron treatment in 9 ... 12 year old elementary school children with iron deficiency anemia - Dedy Gunadi; Nelly Rosdiana; Bidasari Lubis (Indonesian Pediatric Society Publishing House, 2009)
Background The compliance of iron deficiency anemia treatment that is administered three times daily in children is low. The compliance will be better if therapy is administered once daily. Objective To compare the iron therapy response of once per day vs. three times a day administration in 9-12 year old children with iron deficiency anemia. Methods Children with iron deficiency anemia were randomly allocated into a ferrous sulfate once-daily group or a ferrous sulfate three times-daily group with the same dose of 5 mg/kg /day of elemental iron for 30 days. Iron deficiency anemia was defined as Hb < 12 g/dL (World Health Organization criteria), MCV < 70 fl, RDW > 16 %, Mentzer index > 13 and RDW index > 220. Iron treatment response was characterized by the increase in Hb level 30 days after treatment. Peripheral blood samples were collected at the start and end of the study. Results Ninety seven children were enrolled. There were significant increases in Hb levels in both groups after 30 days of iron therapy, but there was no significant difference in Hb level between the two groups (P=0.55). Conclusion The administration of a once daily dose of ferrous sulfate did not show a significant difference in the increase ofHb levels compared to a three times daily dose.